Thermodynamic Study: C-H Bond Activation of Methane with OsO+ - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
Catalysis plays a critical role in the accomplishment of industrially significant chemical transformations, by requiring less energy investment in underlying processes. Computational chemistry has had a pronounced impact on the understanding of the role of catalysts at the atomic and molecular level, contributing to design of more efficient catalysts. In this study, we compute thermochemical properties attending C-H bond activation of methane by OsO+ and enabling subsequent dehydrogenation and dehydration reactions. It is found that the dehydrogenation channel is thermodynamically more favorable. This study should contribute to the understanding of C-H bond activation using homogeneous catalysis of partial oxidation of natural gas (methane) leading to formation of the easily transported liquid fuel methanol.